Vitalij Mykolaiovych Levenets - "ORTHOPAEDICS, TRAUMATOLOGY; PROSTHETICS", Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
May 27, 2020 marks the 90th anniversary of the birth of an orthopedist-traumatologist, Doctor of Medical Sciences, Professor Vitalij Mykolaiovych Levenets.